ECOLOGICAL BALANCE IN THE QUR’AN: A THEMATIC REVIEW OF VERSES ON CLIMATE CHANGE MITIGATION AND ADAPTATION - Wasilah, Rifqoh; Hayeewaji, Ruslan (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
The phenomenon of climate change and environmental damage caused by human activities has become a global issue that affects the ecological balance of the earth. The Qur’an as a guideline for Muslims contains principles that are relevant to climate change mitigation and adaptation, such as balance, moderation, sustainable management, and reforestation. This study aims to explore and analyze the teachings of the Qur’an related to climate change mitigation and adaptation efforts in the context of maintaining ecological balance. This study uses a qualitative method with a library research approach and thematic interpretation. Data were obtained from primary sources, such as interpretation books, and secondary sources, such as related books and articles. The thematic approach of Abd al-Hayy al-Farmāwī and liberating hermeneutics were used to analyze the verses of the Qur’an related to ecology and climate change mitigation. The results of the study show that the Qur’an emphasizes the importance of the principle of moderation in consumption (QS. Al-A'rāf: 31), sustainable resource management (QS. Hūd: 61), readiness and resilience to environmental challenges (QS. Al-Anfāl: 60), and reforestation (QS. Al-An’ām: 99). These principles do not only focus on practical actions but also moral and spiritual aspects as caliphs on earth. The implication of this study is the importance of integrating the teachings of the Qur’an in environmental policies and ecological education to create awareness and shared responsibility in maintaining the balance of the ecosystem for the sustainability of life on earth